Understanding the semantic principles of a political map (تحقیقات کاربردی علوم جغرافیایی)
The attempt to recognize phenomena and affairs has always been a concern of the human mind and has constantly sought to complete this knowledge. The correct recognition is also achieved when the real nature of phenomena is clear to man. The phenomena are based on their own philosophical foundations and, therefore, their understanding requires perception these philosophical foundations and using proper methods of recognition. The map is also a phenomenon that has its own philosophical foundations and by understanding these philosophical foundations, the true meaning and the components that influence its meaning are clarified. Recognizing it correctly requires understanding many of the elements and other factors. To real understanding this phenomenon, one needs to understand beyond what is usually said about it. In this research, we tried to clarify the philosophical foundations of the map and the factors influencing its meaning by using of hermeneutical methodology. The results of this research showed that the map of the ontology aspect is of an objective-subjective nature. Therefore, it should be understood by methodology such as hermeneutics and not explanation. Also, using this method, it is determined that the mapping factors are divided into two categories. Internal factors, such as the choice of the type of projection and cartographic deviations and external factors such as, the mental purpose of the cartographer and the banners, understand map reader from map, and the spaces of thought, power, and so on make up the actual meaning of the map.